The role of cultivar susceptibility and vineyard age in GTD: examples from the Carpathian Basin - Csótó, András; Balling, Péter; Nagy, Antal; Sándor, Erzsébet (Acta Agraria Debreceniensis, 2020)
Grapevine trunk diseases (GTDs) are among the most severe problems in viticulture worldwide. The exact etiology and the role of endophytic microorganisms is not known yet and there is no adequate protection or curative treatment against the disease. Hungarian wine regions are also affected by the disease, and there is restricted information about the rate of infection nation-wide and about the susceptibility of the Hungarian cultivars. The main objectives of our research are to measure the symptom expression and the damage caused by GTDs, to understand the epidemiology and etiology of the disease to establish a foundation of a proper disease management. Cultivar susceptibility groups were created with the aim to allocate some Hungarian cultivars and the role of vineyard age was also examined in symptom expression.